Harmonisasi Regulasi dan Perbaikan Tata Kelola Sumber Daya Alam di Indonesia - Muhajir, Mumu; Sumardjono, Maria SW; Manurung, Timer; Ferdinand, Julius (Komisi Pemberantasan Korupsi, 2019)
The regulatory harmonization review was carried out on 26 laws related to the management of natural resources. The examination is carried out in two levels: The first level is checking the suitability of the material in the legislation that has been inventoried (17 direct sector laws related to natural resources and nine supporting acts) with the principles contained in TAP MPR IX / 2001. The second level is to examine the overlap of norms, policies, and rules in the law related to natural resources. This overlapping inspection process is only carried out on similar or horizontal statutory regulations. The principle of social justice is the least fulfilled principle in the Law Regarding Natural Resources examined. These findings indicate there needs to be a new direction in the change and preparation of regulations related to natural resources.